Laser induced synthesis of nickel alloy (alumel) nanoparticles in liquids - Moura, C. G. (2020)
Pulsed laser ablation in liquids (PLAL) has been growing as a powerful technique for the synthesis of multielement nanoparticles (NPs) such as metal alloys with complex composition. In consequence, there is a great necessity in expanding the current knowledge about alloy NPs formation during this method, aiming to control the chemical composition of produced NPs. In this work, a nanosecond Nd:YAG laser was used to synthesize NPs of a novel nickel (Ni) alloy, and a brief description regarding the influence of liquid media in size and stability of produced nanoparticles is presented. The results showed great stability in the colloids produced in isopropanol medium without using a surfactant, whereas this environment allowed the production of smaller nanoparticles.